2008
DOI: 10.1534/genetics.108.092478
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen Identifies New Regulators of Steroid-Triggered Programmed Cell Death in Drosophila

Abstract: The steroid hormone ecdysone triggers the rapid and massive destruction of larval tissues through transcriptional cascades that culminate in rpr and hid expression and caspase activation. Here we describe the use of genetic screens to further our understanding of this steroid-triggered programmed cell death response. Pupal lethal mutants were screened for specific defects in larval salivary gland destruction. A pilot screen using existing P-element collections resulted in the identification of mutations in kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…The UAS-Atg1 K38Q stock was generated in the Nuefeld laboratory (Scott et al 2007). All PSG mutations were generated in an EMS-mutagenesis screen on the third chromosome (Wang et al 2008). The allelic combinations used here for phenotypic and molecular analysis of each PSG locus are underlined in Table 1.…”
Section: Drosophila Strainsmentioning
confidence: 99%
See 4 more Smart Citations
“…The UAS-Atg1 K38Q stock was generated in the Nuefeld laboratory (Scott et al 2007). All PSG mutations were generated in an EMS-mutagenesis screen on the third chromosome (Wang et al 2008). The allelic combinations used here for phenotypic and molecular analysis of each PSG locus are underlined in Table 1.…”
Section: Drosophila Strainsmentioning
confidence: 99%
“…The PSG mutations identified in this manner map to the following 10 genes: belle (bel), brwd3/ ram, E93 (Eip93F), headcase (hdc), mdh2, med12, med24, pak, psg2, and reptin (rept) ( Table 1). Of these, the mapping of PSG mutations in belle (Ihry et al 2012) and in med24, mdh2, and psg2 (Wang et al 2008) have been reported. The remaining 19 PSG loci complemented all publicly available lethal mutations in their respective regions and were not pursued further.…”
Section: Mapping Mutations With a Psg Phenotypementioning
confidence: 99%
See 3 more Smart Citations